Optimization of IP networks with fast reroute mechanisms - Rodrigues, Miguel Filipe Ramalho (2015)
This dissertation studies strategies for assigning costs to the interfaces of routers inside an IP network to potentiate the use of Loop-Free Alternates (LFA). LFA is a fast reroute mechanism that has been recently deployed in commercial routers. This mechanism allows routers to forward traffic through alternative paths right after the detection of a network failure, avoiding a higher loss of packets during the network’s recovery process. The problem is that this mechanism does not usually provide coverage to all possible failures. Moreover, repair paths may lead to congestion and even forwarding loops. An application was developed that, given a network topology and its supporting traffic matrix, allows to find IGP costs that improve the network performance when employing this mechanism. The implemented strategies try to minimize situations where the use of repair paths leads to micro-loops or link overloads, thus preserving the quality of the service. The computational results show that it is possible to minimize the effects of a failure through an intelligent choice of costs. It is also possible to conclude that, for the majority of cases, increasing the LFA coverage of a network is not the best strategy. Depending on the available resources, it becomes often necessary to sacrifice this coverage to obtain better performance levels.